La lucha de clases en la antigua Grecia (G. E. M. de Ste. Croix, The Class Struggle in the Ancient Greek World, from the Archaic Age to Arab Conquests, Londres, Duckworth, 1981, XI +732 pp.). - Plácido, Domingo (Gerión. Revista de Historia Antigua, 1983)
Sin resumen